Analysis of 270 fetuses with non‐visualization of cavum septi pellucidi and vergae on in‐utero magnetic resonance imaging. (2nd November 2020) - Griffiths, P. D.; Jarvis, D.
ABSTRACT: Objective: To analyze a large retrospective cohort of fetuses in which the cavum septi pellucidi and vergae (CSPV) was not present or was not in its expected position on in‐utero magnetic resonance imaging (iuMRI), in order to describe the possible causes of that finding and provide a diagnostic approach to assess such cases in clinical practice using iuMRI. Methods: This was a retrospective study of fetuses that underwent iuMRI at a single institution, over an 18‐year period (2000–2017 inclusive), in which the CSPV was not visualized or was abnormal. All iuMRI studies were reviewed and classified as CSPV being not present, disrupted (visualization of remnants of an otherwise normally placed CSPV) or malpositioned (CSPV was present, but not in its expected position). We describe the neuropathology present in each of the groups. Results: Of the 270 fetuses that met the inclusion criteria, the CSPV was described as malpositioned in 150 (56%), disrupted in 71 (26%) and not present in 49 (18%). Malpositioned CSPV was present only in cases with agenesis of the corpus callosum and three specific patterns of malpositioning are described, depending on the location of the leaflets of the CSPV and fornix. Disrupted CSPV was present in fetuses with hydrocephalus or pathologies causing extensive brain parenchymal injury. Not present CSPV was found in cases with holoprosencephaly or when absence of the CSPV appeared to be an isolated finding. Conclusion: We have described a large cohort of fetuses with non‐visualization of a normal CSPV on iuMRI and present a categorical classification system based on the CSPV being not present, disrupted or malpositioned. This approach should help in the diagnosis of the underlying cause of a CSPV abnormality. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.